Women Participation in Eri culture with Special Reference to Kamrup District of Assam - Rabha, Pulak; Saikia, Monimala (Indian Journal of Extension Education, 2021)
A study was conducted during 2017-18 in Kamrup district of Assam to know the participation of women in eri culture. Data were collected purposively from 120 women engaged in eri culture through personal contact method by using the pre-structured interview schedule from three development blocks viz., Chhaygaon, Rampur and Chayani Borduwa. It was revealed that all the women were involved in eri silkworm rearing, followed by feeding, bed cleaning and moulting care (95.83%), leaf harvesting (91.67%), cooking of cocoon and spinning (88.33%) and disinfection (85.00%). A total of 81.67 per cent women faced the problem of leaf crisis during winter months. Participation of women in decision making varied from procurement of disease free laying (85.83%) to nutrient management (27.50%). The study also inferred that training need is prominent in most of the activities of eri culture.
Keywords: Women; Eri culture; Participation; Feeding; Spinning; Training